Moderasi Beragama dalam Kehidupan Sosial Masyarakat Samin di Kabupaten Blora - Khoirunisa, Nabila; Falaq, Yusuf (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2025)
This research focuses on examining the value of religious moderation implemented in the lives of the Samin people in Blora. The Samin community has typical teachings the religion of Adam, such as placing the value of honesty and simplicity as the main principles in their social interactions. This study aims to describe the pattern of religious moderation that is reflected in the social relations of the Samin community with the surrounding Muslim community. The method used is qualitative research with an interactive approach. Data collection techniques were obtained through observation, interviews, documentation, and literature study. The research location was Klopoduwur Village, Banjarejo District, Blora Regency. The results showed that the Samin community is able to apply the value of religious moderation in social interaction through the tradition of kenduren, earth alms, and mutual cooperation without distinguishing differences in beliefs. This shows that the Samin community is able to build harmony in the midst of diversity of beliefs through the preservation of local culture. With this, it can be concluded that the Samin community can carry out a harmonious social life through cooperation without causing conflict despite having different beliefs.